Synchronous Mobile Robots Formation Control - Mohd Razali Mohamad Sapiee; Khalil Azha Mohd Annuar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Synchronous mobile robots formation control is one of the most challenging and interesting fields in robotics. The mobile robots communicate with each other through wireless communication to perform similar movement. This study analyzed two mobile robots that can perform synchronous movement along a shaped path. A square shape is set as a path for the mobile robot movements. The front robot being the leading robot transmits the instruction of its movement to the robot behind it, acting as the following robot through a wireless communication. The instruction sent by the leading robot is received by the following robot through a program embedded in the leading robot microcontroller which then drives the following robot to move and imitates the movement of the leading. The algorithm for the movement is tested on the hardware and the results of the experiment are included to verify the effectiveness of the proposed method.